Legal Protection for Disability Workers in Semarang: Case Study at PT. Samwon Busana Indonesia - Indarti, Retno; Masyithoh, Novita Dewi; Nurhayati, Tri (Universitas Islam Negeri Walisongo Semarang, 2020)
The purpose of this study is to measure legal protection and employment opportunities for persons with disabilities who work in various companies in the city of Semarang, Central Java. As is known, the right to work for citizens is regulated in Article 27 Paragraph 2 of the 1945 Constitution, which mandates the right of citizens to get a decent job and life. Every citizen has the same rights and the state (government) has regulated these rights in terms of obtaining employment without exception, including persons with disabilities. This study uses a juridical-empirical (non-doctrinal) approach, which examines how employment opportunities and legal protection of persons with disabilities in the city of Semarang, especially in PT. Samwon Clothing Indonesia. Primary data sources were obtained from PT. Samwon Busana Indonesia through interviews, secondary data in the form of legal material. Data Collection Method with Interview and Documentation methods, Data Analysis is done by a descriptive method. The results showed that employment opportunities for workers with disabilities in the city of Semarang, especially in PT Samwon Busana Indonesia had fulfilled one percent of the total employees. The total disability workers at the company are 14 out of a total of 1317 employees. In terms of legal protection, all employees both with disabilities and do not get the same rights and opportunities to be treated fairly. In addition, fulfillment of the rights of workers with disabilities is also fulfilled without discrimination.